Redesign ship fishing village district meskom Bengkalis to minimize barriers - Pilipus Tampubolon; Syaifudin '; Ronald M. H (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in April to November 2013 at the village ofMeskom as the location of sampling and laboratory Department of fisheriesresources utilization of ship waters as the place of processing of the data. TheSurvey was conducted on several ships to search for the main vessel size, then thesize of the ship's main design into ships fishing with either using the programmaxsuf. The prisoners in the analysis by using hullspeed. After the detainee wasfound then made changes to reduce the barriers to desan ship. This research usingthe method of survey aimed at finding great boat barriers modifications resultsfisheries ship line plans exsisting. The results showed that the modifications to thevessel's fishing in the village of Meskom the level of change in 5% and themethods used and the method of Holtrop method Van Oortmeersen.Keywords: redesigning of a ship fishery in the village of meskom